Incidence and Risk Factors of Colistin-Induced Nephrotoxicity Associated with The International Consensus Guidelines for the Optimal Use of the Polymyxins: A Retrospective Study in a Tertiary Care Hospital, Saudi Arabia - Fawaz M. Alotaibi; Bashayer M. Alshehail; Zainab A. H. Al Jamea; Royes Joseph; Amal H. Alanazi; Najla A. Alhamed; Reyouf S. Alqarni (MDPI AG, 2022)
Background: Colistin is an effective therapy against multidrug-resistant gram-negative bacteria. However, nephrotoxicity is a major issue with its use. Objective: We aimed to evaluate the incidence and the potential risk factors of nephrotoxicity in colistin-treated patients. Methods: A retrospective cohort study was conducted. All adult patients aged 18 years and older who received colistin for ≥72 h were included in the study, while end-stage kidney disease patients requiring dialysis or had renal transplants were excluded. The incidence and severity of acute kidney injury (AKI) were assessed based on the Kidney Disease Improving Global Outcomes (KDIGO). Result: Out of 128 patients who received colistin, 51.56% of them have experienced AKI. The incidence was increased among oldest patients (above 80) and those who did not receive the appropriate dose (p-value = 0.0003). In addition, the median time until the AKI occurred was 10 days after receiving the colistin treatment. Rates of AKI in patients with previous AKI (71.7%) were three times higher than patients who did not previously experience AKI (HR = 2.97, 95% CI [1.8-4.8]). Conclusions: Nephrotoxicity is a significant issue among patients who receive colistin in the hospital, especially among older patients and those who did not receive the appropriate dose. As a result, healthcare providers should play a major role in colistin dosing, especially among the older adult population.